2002
DOI: 10.1023/a:1016103131408
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: With the premise that oxygen free radicals may be responsible for the severity and complications of diabetes, the level of antioxidant enzymes catalase (CAT), superoxide dismutase (SOD) and glutathione peroxidase (GPx) as well as the oxidative damage were examined in the tissues of control, diabetic and treated rats. After 3 weeks of diabetes, the activity of CAT was significantly increased in heart in diabetes (about 6-fold) but decreased in liver. The SOD activity decreased significantly in liver but increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 211 publications
(52 citation statements)
references
References 30 publications
6
45
1
Order By: Relevance
“…Even though vanadium may participate in Fenton-like reactions [9], together with the proposed mechanisms of vanadate action that involves its bioreduction and ROS production [15,18,19,40], our results point out to a depression in the overall rate of ROS production. This observation is in good agreement with previous reports showing that vanadate supplementation diminished oxidative stress in certain experimental conditions, such as in rat-induced hepatocarcinogenesis [23] and in rat diabetic tissues [41]. Regarding superoxide anion radical production in mitochondrial fraction, once again it was observed that metavanadate and decavanadate promoted opposite effects.…”
Section: Resultssupporting
confidence: 92%
“…Even though vanadium may participate in Fenton-like reactions [9], together with the proposed mechanisms of vanadate action that involves its bioreduction and ROS production [15,18,19,40], our results point out to a depression in the overall rate of ROS production. This observation is in good agreement with previous reports showing that vanadate supplementation diminished oxidative stress in certain experimental conditions, such as in rat-induced hepatocarcinogenesis [23] and in rat diabetic tissues [41]. Regarding superoxide anion radical production in mitochondrial fraction, once again it was observed that metavanadate and decavanadate promoted opposite effects.…”
Section: Resultssupporting
confidence: 92%
“…The formation of lipid peroxides was evaluated in the homogenates of the whole kidney. The formation of malondialdehyde (MDA), an end product of fatty acid peroxidation, was measured spectrophotometrically at 532 nm by using a thiobarbituric acid reactive substance mainly by the method of Genet et al [12]. …”
Section: Methodsmentioning
confidence: 99%
“…Diabetes is associated with increased oxidative stress as reflected in an increased presence of lipid peroxidation products (Jennings et al 1987;Rosen et al 2001;Siddiqui et al 2005;Genet et al 2002). Like in aging increased oxidative stress appears to be the result of increased formation of ROS, reduction in ROS scavengers or both (Moorthy et al 2005a, b;Baquer et al 1990).…”
Section: Diabetic Neuropathy-peripheral and Central Nervous Systemmentioning
confidence: 99%
“…This process in which glucose is oxidized in the presence of free metal ion, leads to superoxide and hydroxyl radical release, and finally causes protein oxidation (Wolff et al 1991;Wolff and Dean 1987). The activity of ROS scavenger compounds like glutathione, catalase and superoxide dismutase may be affected by diabetes (Wohaieb and Godin 1987;Genet et al 2002). Decrease in ROS scavenging compounds may be due to the direct affect of diabetes and aging on scavenger production or activity, like enhanced protein glycation may be responsible for the reduced enzymatic anti-oxidant activity of superoxide dismutase Mohamad et al 2004).…”
Section: Diabetic Neuropathy-peripheral and Central Nervous Systemmentioning
confidence: 99%